2017
DOI: 10.1016/j.catena.2017.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Controlling rainfall-induced soil loss from small experimental plots through inoculation of bacteria and cyanobacteria

Abstract: Soil erosion is a major limitation for achieving sustainable development. Controlling soil detachment in initial stage of soil erosion induced by rainfall is necessary. Several organic and inorganic amendments have been used to reduce rainfall-induced erosion. Meanwhile, the impact of soil microorganisms has been approved on improving soil aggregation by previous studies. However, studying the feasibility of inoculation of soil microorganisms to reduce soil loss by rainfall-induced erosion has not been conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(19 citation statements)
references
References 49 publications
2
17
0
Order By: Relevance
“…The erosion protection offered by the cyanobacteria increased with the number of days over which the CBC was allowed to develop. The CBCs in this study were grown for 60 days and reduced soil erosion splash loss by 83%–95% for 2‐mm rainfall, and 91%–94% for 2 + 5‐mm rainfall ( t = 7), which compares well with Kherifam et al's () findings that 60‐day‐old cyanobacterial crusts reduced soil loss by 99% (Table ). Chamizo et al () found that cyanobacterial crust growing on a sandy loam soil only reduced soil losses by 50% compared to CBC on a silty loam where soil loss was reduced by 90%.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The erosion protection offered by the cyanobacteria increased with the number of days over which the CBC was allowed to develop. The CBCs in this study were grown for 60 days and reduced soil erosion splash loss by 83%–95% for 2‐mm rainfall, and 91%–94% for 2 + 5‐mm rainfall ( t = 7), which compares well with Kherifam et al's () findings that 60‐day‐old cyanobacterial crusts reduced soil loss by 99% (Table ). Chamizo et al () found that cyanobacterial crust growing on a sandy loam soil only reduced soil losses by 50% compared to CBC on a silty loam where soil loss was reduced by 90%.…”
Section: Discussionsupporting
confidence: 88%
“…As the soils had only very fine aggregates, the absolute reduction of SSR due to disaggregation was small and the primary determinant of SSR, particularly after the 2‐mm rainfall applications, was raindrop impact and the microtopography associated with the development of a sieving crust (Bullard et al, ). The presence of CBCs before the rainfall treatment made the soil surface rougher than the abiotic soil, but despite being early successional stage, this was sufficient to protect the soil from raindrop impact and erosion, as has been demonstrated elsewhere during inoculation studies (Kheirfam et al, ; Sadeghi et al, ). The surface roughness of the soils with CBCs did increase very slightly with each treatment (slight increases in RR and TR).…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…The main parts of soils in case study are soils made by erosion of calcareous stones [14]. It should be mentioned that in Kheiroud kenar region [13], four main soil category of soil can be observed as following: contain of Entisols, Inseptisols, Vertisols and Alfisols [27,20].…”
Section: Case Studymentioning
confidence: 99%